1999
DOI: 10.1002/(sici)1521-3951(199911)216:1<683::aid-pssb683>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dislocations and Stress in AlGaN on Sapphire Using a Low Temperature Interlayer

Abstract: In organometallic vapor phase epitaxial growth of AlGaN on sapphire, the role of the low-temperature-deposited interlayers on a high-temperature-grown GaN layer was investigated by in-situ stress measurement, X-ray diffraction, and transmission electron microscopy. Crack-free and lowdislocation-density AlGaN with the whole compositional range has been realized on the sapphire substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 7 publications
0
37
1
Order By: Relevance
“…10 Several groups reported on different approaches to grow thick AlGaN layers over GaN buffers. 11,12 However, the use of GaN layers drastically decreases the light extraction efficiency in deep-UV emitters due to strong absorption. We now report an approach of using a set of AlN/AlGaN superlattices ͑SLs͒ to reduce the biaxial tensile strain and successfully grow 3.0-m-thick Al 0.2 Ga 0.8 N on sapphire without any cracks.…”
mentioning
confidence: 99%
“…10 Several groups reported on different approaches to grow thick AlGaN layers over GaN buffers. 11,12 However, the use of GaN layers drastically decreases the light extraction efficiency in deep-UV emitters due to strong absorption. We now report an approach of using a set of AlN/AlGaN superlattices ͑SLs͒ to reduce the biaxial tensile strain and successfully grow 3.0-m-thick Al 0.2 Ga 0.8 N on sapphire without any cracks.…”
mentioning
confidence: 99%
“…SEM analysis revealed, that the cracked surface consisted of pieces of AlGaN crystals of about 10 mm in size. Amano et al [5] experimentally showed, that a thin low-temperature ($500 C) AlN interlayer reduced stress in the AlGaN layer, preventing crack generation in the AlGaN films. The present results indicate, that thin HT-AlN also significantly reduces the tensile stress in the AlGaN layer and is useful to grow crack-free high quality AlGaN films.…”
Section: Resultsmentioning
confidence: 99%
“…15 It was found that the LT interlayer was effective in redefining the in-plane lattice parameter through strain relaxation. 16,17 However, it was also observed that the LT nucleation layer was less effective for the growth of highquality AlGaN than for GaN. 18 Unlike trimethylgallium (TMGa) used in GaN growth, trimethylaluminum (TMAl) used in AlGaN growth has a much stronger pre-reaction with ammonia (NH 3 ) and Al atoms do not have enough time to move to energetically favorable lattice sites due to their low surface mobility.…”
Section: Growth Of High-crystal-quality Algan Epilayersmentioning
confidence: 99%